Degradability of Epoxy/Sisal Fiber Composites via Simulated Soil - Bandeira, C.F.; Montoro, S.R.; Faria, S.T.; Moreira, P.R.S.; Pereira, A.C.C.; Oliveira, L.F.; Milanese, A.C. (Journal of Research Updates in Polymer Science, 2017)
The increase in the disposal of new polymeric materials is growing considerably in recent years, causing a major environmental impact. In view of this factor, many researchers have been studying and producing biodegradable composites whose shorter time to degradation reduces the volume of waste in landfills. Reinforcements made from natural fibers, especially sisal, has been much used in these new composites due to their low density, because they are derived from renewable source, are not toxic and their low cost compared to synthetic fibers. In view of this need, this study evaluated an epoxy/sisal composite via TGA (Thermogravimetric Analysis), DSC (Differential Scanning Calorimetry), the impact resistance and the mass variation evaluation before and after exposure in simulated soil for a period of 8 weeks.